Preparation of SiO2-diamond composites by spark plasma sintering - Kitiwan, Mettaya; Katsui, Hirokazu; Goto, Takashi (My University, 2021)
SiO2-diamond composites with 65–85 mass% diamond were fabricated by spark plasma sintering at 1873 K under 130 MPa for 300 s using bimodal diamond particle size of 2 and 25 µm in diameter. The diamond particles were coated with a SiC layer by chemical vapor deposition. The effects of diamond content on relative density, microstructure, and Vickers hardness of the SiO2-diamond composites were investigated. The SiO2-diamond composites exhibited relative density of 96%, and Vickers hardness of 36.2 ± 3.6 GPa at 75 mass% diamond content.
Keywords: bimodal; CVD; Diamond; SiC; SiO2; spark plasma sintering